Using ELSA Speak Application as A Medium to Improve English Speaking Skills - Hasbi, Muhamad; Nursaputri, Eka (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study aims to assess how the ELSA Speak app helps improve the English-speaking skills of eighth-grade students at an Indonesian Islamic Junior High School and measure how much their speaking skills improve after using the app. The participants in this research included one English teacher and 15 eighth-grade students. The research was conducted using a Classroom Action Research (CAR) methodology, combining both qualitative and quantitative approaches. Qualitative data were gathered through photographs and observation checklists, while quantitative data were derived by comparing students' pre-test and post-test results. In the first cycle of the study, the average pre-test score was 53.93, which increased to 62.47 in the post-test. In the second cycle, students' performance improved further, with the pre-test score rising to 61.67 and the post-test reaching 74.87. The statistical analysis revealed a significant improvement in students' speaking abilities, as indicated by the t-test results. The t-test value for the second cycle (7.665) was notably higher than that of the first cycle (5.502), demonstrating a significant impact on students' speaking skills. The overall improvement from the first to the second cycle was 46.66%. Based on these findings, the study concludes that the use of the ELSA Speak application has a substantial positive effect on the students’ English-speaking proficiency.